Влияние формы импульса возбуждения на силовые и скоростные показатели линейных ударных электромеханических преобразователей индукционного и электродинамического типов - Болюх, Владимир Федорович; Щукин, Игорь Сергеевич (Национальный технический университет "Харьковский политехнический институт", 2020)
На основе математической модели, учитывающей взаимосвязанные электрические, магнитные, механические и тепловые процессы, исследовано влияние колебательно-затухающего, однополупериодного и апериодического импульсов возбуждения на показатели линейных ударных электромеханических преобразователей (ЛУЭП) индукционного и электродинамического типов в режимах холостого хода, нагрузки и торможения. Показано, что наиболее высокие скоростные показатели возникают в режиме холостого хода, когда обмотка якоря разгоняется без исполнительного элемента, а наиболее высокие силовые показатели – в режиме торможения, при котором якорь неподвижен. Установлено, что наибольшую скорость (18,95 м/с) обеспечивает ЛУЭП электродинамического типа при возбуждении однопополупериодным и колебательно-затухающим импульсами в режиме холостого хода. Наибольший КПД (29,2 %) имеет ЛУЭП электродинамического типа при возбуждении однополупериодным импульсом в режиме холостого хода. Наибольшую величину импульса электродинамических усилий (19,2 Н∙с) развивает ЛУЭП индукционного типа в режиме торможения. Наибольшее превышение температуры обмотки индуктора (1,7 К) происходит в ЛУЭП индукционного типа в режиме холостого хода, а наибольшее превышение температуры обмотки якоря (0,7 К) – в ЛУЭП электродинамического типа в режиме торможения.

Purpose. To study the effect of vibrational-damping, half-wave and aperiodic excitation pulses on the power and speed parameters of a linear shock electromechanical transducer (LSET) of induction and electrodynamic types when operating in idle, load and braking modes. Methodology. Тo account for the interconnected electrical, magnetic, mechanical and thermal processes, as well as a number of nonlinear dependencies, a mathematical chain model with lumped element parameters is used. This model allows you to quickly carry out the calculation of indicators and characteristics of the LSET with varying the shape of the excitation pulse and the operating mode. Results. The electrical and mechanical characteristics, power and speed parameters of the induction and electrodynamic type LSETs are obtained upon excitation of a vibrationally damped, half-wave and aperiodic excitation pulse when operating in idle, load and braking modes. Originality. It is shown that the highest speed indicators occur in idle mode, when the armature winding accelerates without an actuator, and the highest power indicators - in braking mode, in which the armature is stationary. Practical value. It has been established that the highest speed (18.95 m/s) is developed by an electrodynamic type LSET excited by single-half and vibrationally-damped pulses in the idle mode. The highest efficiency (29.2%) is developed by an electrodynamic type LSET upon excitation by a half-wave pulse in idle mode. The largest magnitude of the pulse of electrodynamic forces (19.2 N∙s) is developed by an induction-type LSET in braking mode. The largest excess of the temperature of the inductor winding (1.7 K) occurs in the LSET of the induction type in idle mode, and the largest excess of the temperature of the armature of the armature (0.7 K) is in the LSET of the electrodynamic type in braking mode.
Influence of the shape of the excitation pulse on the power and speed indicators of linear shock electromechanical converters of induction and electrodynamic types
Keywords: режим холостого хода; нагрузки и торможения; idle mode; load and braking